2021
DOI: 10.48550/arxiv.2106.05367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulling back information geometry

Abstract: Latent space geometry has shown itself to provide a rich and rigorous framework for interacting with the latent variables of deep generative models. The existing theory, however, relies on the decoder being a Gaussian distribution as its simple reparametrization allows us to interpret the generating process as a random projection of a deterministic manifold. Consequently, this approach breaks down when applied to decoders that are not as easily reparametrized. We here propose to use the Fisher-Rao metric assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In the electronic arXiv preprints [1,2] and their formally published version [3], the authors investigated the geometry induced by the Fisher-Rao metric on the parameter space of the Dirichlet distributions in statistics theory, showed that the parameter space is a Hadamard manifold (that is, the manifold is geodesically complete and has negative sectional curvature everywhere), and demonstrated that the Fréchet mean of a set of the Dirichlet distributions is uniquely defined in the geometry. The papers [1][2][3] have been cited in [4][5][6][7][8][9][10][11][12][13][14][15][16]. This means that the papers [1][2][3] have attracted great interest from more and more mathematicians in a short time.…”
Section: Fisher-rao Geometry Of Dirichlet Distributionsmentioning
confidence: 99%
“…In the electronic arXiv preprints [1,2] and their formally published version [3], the authors investigated the geometry induced by the Fisher-Rao metric on the parameter space of the Dirichlet distributions in statistics theory, showed that the parameter space is a Hadamard manifold (that is, the manifold is geodesically complete and has negative sectional curvature everywhere), and demonstrated that the Fréchet mean of a set of the Dirichlet distributions is uniquely defined in the geometry. The papers [1][2][3] have been cited in [4][5][6][7][8][9][10][11][12][13][14][15][16]. This means that the papers [1][2][3] have attracted great interest from more and more mathematicians in a short time.…”
Section: Fisher-rao Geometry Of Dirichlet Distributionsmentioning
confidence: 99%